Automatic Students Presence System Based on Face Recognition Using Surveillance Camera - B. Nugroho; E.Y. Puspaningrum; Saputra, W. S. J. (Nusantara Science and Technology Proceedings)
Today, implementation of information technology has expanded to various fields including education. Implementation of information technology in education has evolved from the most basic systems to complex systems. In education, there are much research about Implementation of information technology, start from technology itself to user impact and society. The biometric presence system is one of the implementations of technology that has implemented in several government and private institutions. Biometric presence systems besides using fingerprints can also use faces. Presence systems using faces require simple hardware such as digital cameras and integrated systems. Face based presence usually uses a camera that is directly attached to a presence device, and the face must be directly in front of the camera. The face will be recognized using surveillance cameras to replace ordinary presence cameras. A face detection system added to support the initial process in face recognition. Presence using this surveillance camera will be tested in a study room at the Universitas Pembangunan Nasional "Veteran" Jawa Timur, and will be analyzed about the accuracy and precision of the system. Based on the experiments that have been done, face recognition performance is 72.40%. This accuracy is included in the medium category. This result is still not optimal. The optimization process needs to be done in future research, by analyzing system weaknesses, modification of facial recognition methods, and pre-processing techniques for face data.